Acupuncture at Zusanli (ST36) for Experimental Sepsis: A Systematic Review. (7th March 2020) - Lai, Fang; Ren, Yang; Lai, Chengzhi; Chen, Rui; Yin, Xuelian; Tan, Caixia; Li, Jiansen; Yang, Chunmei; Liang, Guorong; Li, Jun; Zeng, Ruifeng
Abstract : Background . Sepsis is a global major health problem with high mortality rates. More effective therapy is needed for treating sepsis. Acupuncture has been used for various diseases, including severe infection, in China for more than 2, 000 years. Previous studies reported that acupuncture at Zusanli (ST36) might be effective in treating sepsis, but the efficacy and the quality of evidence remain unclear since there is no systematic review on acupuncture at ST36 for sepsis. Methods . Seven databases were searched from the inception of each database up to May 2019. Ultimately, 54 studies using acupuncture at ST36 for the treatment of experimental sepsis were identified in both English and Chinese literature with systematic review procedures. Results . Acupuncture might be useful in reducing injuries induced by sepsis in cardiac, lung, kidney, liver, gastrointestinal tract, and immune system. Its potential mechanisms for antisepsis might include reducing oxidative stress and inflammation, improving microcirculatory disturbance, and maintaining the immune balance mediated by dopamine. However, the positive findings should be interpreted with caution due to poor methodological quality and publication bias. Conclusion . Acupuncture at ST36 might be a promising complementary strategy for controlling sepsis inflammation, yet further studies are needed.